Global research trends in signaling pathways of spasmolytic polypeptide-expressing metaplasia pathogenesis: a bibliometric analysis - Xu, Qiumiao; Dai, Zhijiang; Peng, Chengjin; Yan, Qinghong; Chen, Xiaoting; Liu, Tongwei; Zhang, Ran; Huang, Guoxin; Liu, Xinyao; Wang, Jingbin (Frontiers in Oncology, 2025)
BackgroundSignaling pathways associated with spasmolytic polypeptide-expressing metaplasia (SPEM) pathogenesis play a critical role in disease development, particularly in gastric cancer precursor lesions. However, global research trends in signaling pathways in SPEM pathogenesis remain undetermined. This study aims to fill this gap by conducting a comprehensive bibliometric analysis to map the field, identify key insights, and guide future research directions.MethodsArticles and reviews were retrieved from the Web of Science Core Collection up to June 8 2025. Bibliometric analysis and knowledge mapping were conducted via CiteSpace and VOSviewer.ResultsA total of 89 papers from 221 institutions, 719 authors, and 56 journals across 21 countries/regions were included. The number of publications is growing slowly. Gastroenterology led in publication and co-citation counts. The United States and China were at the top in terms of publication numbers. Goldenring JR emerged as the most co-cited and most published author. Key findings indicate limited collaboration despite a foundation of ten pivotal articles. Research elucidating gene-pathway interplay and cytokine roles in SPEM pathogenesis has consequently sharpened the focus on developing pharmacological agents that target these pathways, defining a pivotal new direction for combating gastric precancerous lesions.ConclusionBy systematically reviewing signaling pathways in SPEM pathogenesis, this study provides critical guidance for future research strategic planning and collaboration. It highlights the urgent need for strengthened interdisciplinary and global partnerships to drive progress.